Analysis of changes and criticality level of mangrove forest ecosystem as a basis for rehabilitation downstream of Poso Watershed Area, Central Sulawesi, Indonesia - RENDY AHMAD YANI; NAHARUDDIN NAHARUDDIN; BAU TOKNOK; ADAM MALIK; AKHBAR AKHBAR; SUDIRMAN DAENG MASSIRI; SAMSURIZAL M. SULEMAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yani RA, Naharuddin N, Toknok B, Malik A, Akhbar A, Massiri SD, Suleman SM. 2024. Analysis of changes and criticality level of mangrove forest ecosystem as a basis for rehabilitation downstream of Poso Watershed Area, Central Sulawesi, Indonesia. Biodiversitas 25: 3179-3188. Effective mangrove forest management requires accurate data and information on changes and criticality levels within the ecosystem. This research aimed to assess changes and determine the criticality levels of mangroves using the Normalized Difference Vegetation Index (NDVI) as a foundation for sustainable conservation and rehabilitation efforts. Multi-temporal satellite data was utilized to analyze mangrove forest cover changes between 2013 and 2023, while NDVI transformations were applied to evaluate forest vegetation density and criticality levels. The results identified five families and 11 mangrove species in the downstream Poso Watershed, Central Sulawesi, Indonesia. These included Avicennia marina (Forssk.) Vierh. from the Avicenniaceae family, Bruguiera gymnorrhiza (L.) Lam., Bruguiera cylindrica (L.) Blume, Ceriops tagal (Perr.) C.B.Rob., Rhizophora apiculata Blume, Rhizophora mucronata Lam., and Rhizophora stylosa Griffith from the Rhizophoraceae family, Sonneratia alba Sm. from the Sonneratiaceae family, Xylocarpus granatum J.Koenig and Xylocarpus rumphii (Kostel.) Mabb. from the Meliaceae family, and Nypa fruticans Wurmb from the Arecaceae family. The mangrove canopy density downstream of the Poso Watershed was categorized into dense (55,652 ha), moderate (56,863 ha), and rare (67,578 ha). The R. stylosa was the dominant species. The criticality assessment classified the mangrove forest as largely damaged, with a TSV1 value of 190 on a scale of 167-233. Severely damaged or very critical areas covered 35,836 ha (6.58%), damaged or critical areas encompassed 401,462 ha (73.68%), and 107,546 ha (19.74%) were classified as not damaged or not critical. The ecosystem damage was further assessed through vegetation density, with moderate density recorded at 1,259 trees/ha and rare density at 360 trees/ha. Monitoring these changes and criticality levels is essential for successful rehabilitation and demonstrates a strong commitment to sustainable conservation.